An introduction to climate change in management education: An individual-level approach - Cathy A. Rusinko (Organization Management Journal (OMJ), 2024)
Purpose This study aims to introduce management students to climate change by providing them with an opportunity to address it in their own lives, through a class exercise. Design/methodology/approach An in-class exercise was designed, carried out and described in this study. Student teams were assigned different questions on how to address major causes of climate change. Each team did research to generate answers, and ranked their answers based on the speed of implementation. Teams reported their answers to the class. The instructor facilitated a debriefing session, during which all responses were ranked with respect to other variables, including cost savings, time savings and lifestyle fit. This exercise uses few resources and can be adapted to different time lengths and teaching/learning formats (e.g. on-ground, virtual, asynchronous online). Findings This exercise can help students to gain an understanding of climate change and its causes and complexities. Students learn how to implement a diverse set of personal actions to mitigate climate change; these can start in the present and continue throughout their lives. In addition, this exercise may help students to make the leap from individual climate change mitigation practices to organizational and societal practices, when they are in the position to do so as future leaders. Originality/value Although classes, exercises, and assignments ask management students to consider issues such as climate change at the organizational level, this individual-level exercise can allow students with limited organizational experience to engage more quickly with climate change and better understand organizational and societal implications in the future. That is, if students first understand how to address climate change in their own lives, they may more effectively transfer and apply that understanding at organizational and societal levels and ultimately synthesize solutions to address climate change in the world.
Keywords: 650; Carbon literacy; Climate change; Experiential exercise; Management education